Chemical Properties of Treated Textile Dyeing Wastewater - H. Hussein, Falah (Asian Journal of Chemistry, 2013)
The main objective of this research was to observe and evaluate the chemical properties of photocatalytic treated textile industrial wastewater to evaluate reusing it again for different purposes such as agricultural irrigation, recreational uses, groundwater recharge, industrial reuse, environmental uses, non-potable urban uses, indirect potable reuse and direct potable reuse. Photocatalytic treatments carried out over a suspension of titanium dioxide (anatase or rutile) or zinc oxide under artificial irradiation. The progress of treatment stages was followed by using different techniques of analysis. The chemical parameters include total hardness (ppm), total alkalinity (ppm), chemical oxygen demand, biochemical oxygen demand, total organic carbon (%) and acidity (pH). The concentration of major anions, such as, chloride (ppm), phosphate (ppm), nitrite (ppm), nitrate (ppm) were determined. The concentration of positive ions, such as, sodium (ppm), potassium (ppm), zinc (ppm), iron (ppm), cadmium (ppm), copper (ppm), nickel (ppm), cobalt (ppm) and manganese (ppm) and were also measured. Significance improvements of all these chemical parameters for all types of treated industrial wastewater were observed. Experimental results throughout the present study have indicated that the total hardness of real and simulated textile wastewater were reduced by more than 70 % after photocatalytic treatments with titanium dioxide and zinc oxide. Alkalinity, which represents the existence of calcium carbonate or magnesium carbonate, is often related to hardness. Results of alkalinity concentration in different types of textile industrial wastewater dyes used in this study were in the range 37.54-76.66 ppm. The percentage of reduction of alkalinity was ranged between 10-22 % for the treated textile industrial wastewater dyes with the different types of catalysts used in this study. The BOD5/COD ratio of treated real wastewater reached 0.691, 0.688 and 0.711 as compared to 0.398 of the raw wastewater when anatase, rutile and zinc oxide used as photocatalyst respectively. Although the decolorization efficiency reaches 100 %, the total organic carbon removal efficiency did not reach that percentage. The results demonstrated 72-87 % of TOC removal after 10 h of irradiation using titanium dioxide (anatase or rutile) and 92 % when zinc oxide was used for the different textile industrial wastewater dyes. The initial pH of simulated and real textile industrial wastewater was in the range 8.41-12.90. All pH values for the photocatalytic treated textile industrial wastewater dyes with anatase; rutile and zinc oxide were reduced to 7.00 ± 0.20. Major anions e.g., chloride, phosphate, nitrite and nitrate were measured after and before photocatalytic treatments. The percentage of removal for these anions was exceeded 90 % and in many cases reached 100 %. However, no significant changes were observed in the concentrations of the major cations, sodium and potassium, after and before photocatalytic treatments for the five textile industrial wastewater dyes used in this article. Real and simulated textile industrial wastewater dyes were also analyzed for zinc, iron, cadmium, copper, nickel, cobalt and manganese using atomic absorption spectrophotometer. No changes were observed in the concentrations of these metals after and before photocatalytic treatments. The heterogeneous photocatalytic degradation of real and another four prepared simulated textile industrial wastewater dyes viz., (Vat yellow, Reactive black, Reactive blue and Cowboy dyes) were carried out on a laboratory scale using three commercial photocatalysts namely, anatase, rutile and zinc oxide.Comparison between the efficiency of the three photocatalysts indicated that their efficiency fell in the sequence: ZnO > TiO2 (anatase) > TiO2 (rutile). However, the amount of zinc oxide required to reach the optimum activity is two times more than that for titanium dioxide (anatase or rutile) and the sequence was changed when the same concentration of mass was used (175 mg L-1). The sequence in such case as follows: TiO2 (anatase) > ZnO > TiO2 (rutile). Generally, the results of this study suggest that the treated wastewater is suitable for domestic, industrial and irrigational purposes.